Correction to: 1, 2(2, 2-dihydroxy Benzelidenamine) Phenyl Complexes as Corrosion Inhibitor for Carbon Steel in Hydrochloric Acid - Najeeb, Dina A; Salman, Taghried A (Al-Nahrain Journal of Science, 2019)
No Abstract.